What is the subject matter of physical education? - Messmer, R. (German Journal of Exercise and Sport Research, 2018)
The school subject Physical Education (PE) deals explicitly with the body and movement. Therefore, it is essential to define the content of PE based on these two aspects. Historically, school is mainly oriented towards the mind, which has recently been named competency. For that reason, the mind-body problem is omnipresent in PE. Additionally, the recent shift to developing competencies in PE is intensifying the dualism of mind and body by opposing knowledge and knowing-how. In a first step, this categorical difference between mind and body will be explained in the course of a philosophical discussion and illustrated with appropriate examples. As will be shown, the mind-body contrast should be considered as a continuum instead of a dualism. Therefore—in a second step—Green`s teaching continuum will give an answer to the question if the subject matter of PE is a combination of cognitive and motor activity or not. In a third step, Dewey`s concept of experience will be outlined, based on which the practice of doing sport is explained and developed. A fourth step will be to develop a complementary curricular model that attempts to connect the two poles "mind" and "body" by linking performance with content standards (forms of sport), based on the current discourse on competencies and standards. In this manner, the presentation of a curricular model for PE overcomes the Cartesian contrast between mind and body. Additionally, it gives an answer to the current discussion about competencies and standards in PE that emanates from other disciplines and should be self-confidently discussed in our own discipline.